Subscribers Satisfaction on Newspaper Agency Service in Kerala - Sanesh C.& Dr. B. Johnson (RA-International Journal of Management & Social Sciences, 2018)
Newspaper subscription and reading is a traditional habit among most of the people living in Kerala. Most of the people in Kerala start their daily routine by reading a newspaper with a cup of tea. Newspaper agent’s service quality must be evaluated by newspaper publishers from the opinion of newspaper subscribers. If subscribers are not happy with the service of newspaper agent and delivery boys it may affect the overall prosperity of the newspaper industry itself. Therefore it is relevant to measure the service quality of newspaper agents. Nowadays readers have more options for getting information on varying issues. It revealed that regarding the distribution matters of newspapers, many of the subscribers are not pleased with the current status. Interestingly publishers are not interested to know from the subscribers regarding delivery related issues.